Konsep Dasar Administrasi dan Manajemen Perspektif Al-Quran - Rhohis Kurniawan; Hamidullah Mahmud (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2024)
This study aims to discuss the concept of administration and management in general, and to view it from the perspective of the Qur'an. By understanding the principles of Qur'anic management, it is hoped that these values ​​can be applied in everyday life, so that a balance is created between achieving worldly and hereafter goals. In addition, this paper also explores how administration and management in Islam are not only oriented towards efficiency, but also on spiritual values ​​that bring benefits to life in the world and the hereafter. The research methodology used in this study is descriptive qualitative research using the library research method. Administration is a joint effort process involving all parties to realize common goals and ideals. The term management actually refers to the process of implementing activities that are completed efficiently with and through the use of others. In the Qur'an, the term management uses yudabbiru, which means organizing, managing, engineering, implementing, taking care of well. Islamic management can be viewed from two sides, namely management as a science and management as an activity. As a science, management is seen as one of the general sciences that was born based on empirical facts that are not related to any values, civilizations (hadharah). However, as an activity, management is seen as a deed that will be held accountable before Allah SWT.